A Critical Study on Sundarbans Described By Amitav Ghosh: Exploring the Ecological and Human Dynamics of Sundarbans (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Sundarbans a difficult place to live for humans, but, atthe same time, a unique habitat for fauna and flora. The mangrove swamps aredominant, and they provide the shelter for many species of animals, which arespecific to the region or very rare in other areas. The example is the RoyalBengal Tiger, a man-eater featuring in “The Hungry Tide” together with severalspecies of dolphins and deadly crocodiles. The novel starts with the meeting of two mainscharacters, Piyali (Piya), an Indian-American field biologist specialized indolphins, and Kanai a sophisticated interpreter and businessman, on the trainto Canning. Piya has a plan to collect data on the life of the rare riverdolphins, which are the subject of her research. Kanai was summoned by hisaunt, Nilima, to the island of Lusibari (he spent there only one summer as aschoolboy), where she runs a charity, to get the package left to him in thewill of his late uncle, Nirmal, a leftist schoolteacher with literaryambitions. Kanai is interested in Piya, and when they part in Canning, heinvites her to Lusibari.